Focal validation mechanism for Lombok earthquake with image analysis of satellite radar and crust movement GPS observation - I Putu Pudja (Center for Science and Technology, IAIN Surakarta, 2020)
Lombok Earthquake on August 5 and August 19, 2018, traces of deformation were analyzed with satellite image data to determine vertical deformation in the form of uplift on the ground surface. Earthquake wave analysis provides data on the mechanism at the epicenter in the form of a fault, the major forces axis in the form of the P axis, as well as the T axis, in addition to location and strength. The results of the focal analysis showed that the Lombok earthquake was an earthquake on the rising fault, the results of satellite radar image analysis showed the corresponding results, where the maximum increase occurred on the lip of the fault block in the form of a hanging wall. The direction of the acting force is indicated by the Axis P, in accordance with the research results of the Lombok earth crust movement, namely the N-NE Direction.